Discrete Verhulst model based on a linear time-varying. Issue 2 (29th July 2014) - Naiming Xie, Dr Yingjie Yang and Dr Chuanmin Mi, Professor; Long, Xia; Wei, Yong; Long, Zhao
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to build a linear time-varying discrete Verhulst model (LTDVM), to realise the convert from continuous forms to discrete forms, and to eliminate traditional grey Verhulst model's error caused by difference equations directly jumping to differential equations. Design/methodology/approach – The methodology of the paper is by the light of discrete thoughts and countdown to the original data sequence. Findings – The research of this model manifests that LTDVM is unbiased on the "s" sequential simulation. Practical implications – The example analysis shows that LTDVM embodies simulation and prediction with high precision. Originality/value – This paper is to realise the convert from continuous forms to discrete forms, and to eliminate traditional grey Verhulst model's error caused by difference equations directly jumping to differential equations. Meanwhile, the research of this model manifests that LTDVM is unbiased on the "s" sequential simulation.